BEHAVIOR OF LANGUAGE STUDENTS TOWARDS EXAMINING INFORMATION ONLINE - Apostol, Rhea Mae; Castillo, Joshua; Terrenal, Gizzelle; Santos, Melody; Belisario, Glyzelle; Martin, Reygie; Diego, Rosemarie; Gammad, Trisha Grace; Paguirigan, Jelly; Lago, Rina Joy; Mallilline, Nicalaine (International Journal of Arts, Sciences and Education, 2022)
This research examined the behaviors of language students towards examining information online. A mixed method design was used and an unstructured open-ended question was also constructed to gather data from the 86 participants from Isabela State University San Mariano Campus. Hence, the thematic approach was also used in this study. The researchers initially planned a platform to gather and collect data to create themes and to analyze the main point of the chosen respondents. The study findings confirmed two themes; report fake news and validate information online. It shows that most of the language students are knowledgeable enough to assess information online to minimize spreading fake news on various platforms. Based on the results of this study, it revealed that students are carefully analyzing the information. It also shows that most of the students tend to analyze facts of the information that they obtained online. Furthermore, because of the proliferation of fake news on the internet, students become more cautious through evaluating the information that they gained from the internet.